2016
DOI: 10.4238/gmr.15037868
|View full text |Cite
|
Sign up to set email alerts
|

PI3K-Akt-mTOR signal inhibition affects expression of genes related to endoplasmic reticulum stress

Abstract: ABSTRACT. PI3K-Akt-mTOR signaling pathway is associated with endoplasmic reticulum (ER) stress. However, it is not clear how this signaling pathway affects the ER stress. The present study aimed to determine whether the PI3K-Akt-mTOR signaling pathway regulates tunicamycin (TM)-induced increases in mRNA levels of genes involved in the ER stress, to help elucidate the mechanism by which this pathway affects the ER stress in primary goose hepatocytes. Primary hepatocytes were isolated from geese and cultured in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 28 publications
(31 reference statements)
2
11
0
Order By: Relevance
“…Evidence has demonstrated that AKT activation positively regulates ER stress via PrPC and Akt-MnSOD pathway in mesenchymal stem cells [31]. Also, PI3K-Akt signal inhibition affects expression of genes related to endoplasmic reticulum stress in primary goose hepatocytes [32]. Thus, our finding that AKT knockdown prevents HG-induced protein expression involved in ER stress activation further confirmed the regulation of AKT on ER stress in renal cells.…”
Section: Discussionsupporting
confidence: 83%
“…Evidence has demonstrated that AKT activation positively regulates ER stress via PrPC and Akt-MnSOD pathway in mesenchymal stem cells [31]. Also, PI3K-Akt signal inhibition affects expression of genes related to endoplasmic reticulum stress in primary goose hepatocytes [32]. Thus, our finding that AKT knockdown prevents HG-induced protein expression involved in ER stress activation further confirmed the regulation of AKT on ER stress in renal cells.…”
Section: Discussionsupporting
confidence: 83%
“…Our previous results revealed that ACE2 downregulation decreased phosphorylation of Akt . As all we known, Akt not only played a pivotal role in glucose and lipid metabolism signalling pathway but also associated with ERS . Evidence showed that suppression of Akt signalling could induce the ERS and subsequent apoptosis .…”
Section: Discussionmentioning
confidence: 85%
“…ERS shares a correlation with the PI3K/Akt/mTOR signaling pathway. Our experimental data revealed that increases in ERS are followed by decreases in PI3K/AKT/mTOR signaling, as well as reductions in chemoresistance; when the PI3K/AKT/mTOR signaling pathway is blocked, autophagy and apoptosis factors are increased, chemotherapy resistance is weakened, and the tumor shrinks [27, 59], which has an important function in autophagy and apoptosis regulation [2, 60, 61]. It has been reported that blocking the PI3K/AKT/mTOR cascade promotes autophagy [62] that inhibiting PI3K/Akt/mTOR signaling promotes cell apoptosis in LC [28], which is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%